Comparative Study on Gas-Sensing Properties of 2D (MoS2, WS2)/PANI Nanocomposites-Based Sensor - Hemalatha Parangusan; Jolly Bhadra; Razen Amer Al-Qudah; Elhassen Cheikh Elhadrami; Noora Jabor Al-Thani (Nanomaterials, 2022)
NH3 is a highly harmful gas; when inhaled at levels that are too high for comfort, it is very dangerous to human health. One of the challenging tasks in research is developing ammonia sensors that operate at room temperature. In this study, we proposed a new design of an NH3 gas sensor that was comprised of two-dimensional (TMDs, mainly WS2 and MoS2) and PANI. The 2D-TMDs metal was successfully incorporated into the PANI lattice based on the results of XRD and SEM. The elemental EDX analysis results indicated that C, N, O, W, S and Mo were found in the composite samples. The bandgap of the materials decreased due to the addition of MoS2 and WS2. We also analyzed its structural, optical and morphological properties. When compared to MoS2 and PANI, the proposed NH3 sensor with the WS2 composite was found to have high sensitivity. The composite films also exhibited response and recovery times of 10/16 and 14/16 s. Therefore, the composite PANI/2D-TMDs is a suitable material for NH3 gas detection applications.